Dynamics of Small Solar System Bodies and Exoplanets - Souchay, Jean J.; Dvorak, Rudolf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book offers an up-to-date overview of current research on Dynamics of Small Solar System Bodies and Exoplanets. In course-tested extensive chapters the authors cover topics of theoretical celestial mechanics, physics and dynamics of asteroids, comets, stability of exoplanets and numerical integration codes applied in dynamical astronomy.
Resonances: Models and Captures -- The Lyapunov Characteristic Exponents and Their Computation -- Asteroid Dynamical Families -- An Introduction to the Dynamics of Trojan Asteroids -- The Physics of Asteroids and Their Junction with Dynamics -- The Gaia Mission and the Asteroids -- Cometary Dynamics -- Dynamical Features of the Oort Cloud Comets -- An Introduction to Common Numerical Integration Codes Used in Dynamical Astronomy -- Dynamical Stability of Extra-Solar Planets.
Keywords: Physics; Differentiable dynamical systems; Mathematical physics; Astrophysics; Physics; Astrophysics and Astroparticles; Mathematical Methods in Physics; Extraterrestrial Physics, Space Sciences; Dynamical Systems and Ergodic Theory